jQuery Recipes A Problem-Solution Approach - Harwani, B. M.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
jQuery is one of today$1 (Bs most popular JavaScript web application development frameworks and libraries. jQuery Recipes can get you started with jQuery quickly and easily, and it will serve as a valuable long-term reference. The book begins with small initial problems that developers typically face while working with jQuery, and gradually goes deeper to explore more complex problems. The solutions include illustrations and clear, concise explanations of the code. Using this book and jQuery, your web sites will be more dynamic and lively.s
jQuery Basics -- Arrays and Strings -- Event Handling -- Form Validation -- Page Navigation -- Visual Effects -- Dealing with Tables -- Ajax -- Using Plugins -- Using CSS.
Keywords: Computer science; Computer Science; Programming Techniques